Notes on the genus Abantis Hopffer, 1855 with description of two new species (Lepidoptera: Hesperiidae, Pyrginae) - Belcastro, Claudio; Oremans, Philippe (Fragmenta entomologica, 2016)
The Afrotropical genus Abantis Hopffer, 1855 includes about 23 species so far, all quite rare. In Evans’ Catalogue of the African Hesperiidae only 14 species were listed but, apart from a few newly discovered ones, some of the subspecies indicated over there have subsequently been raised to species level, although they look very similar in facies with previously recognised taxa. This article shows the presence of an unrecognised species similar to A. lucretia Druce, 1909 in West Africa, namely A. fabiana sp. n., and another one similar to both A. contigua Evans, 1937 and A. elegantula Mabille, 1890 in Central Africa, namely A. torbeni sp. n. The rarity in collections of almost all forest-dwelling Abantis spp. is reported as connected to their habit of flying high in the forest canopy, but the authors have no conclusive evidence of it. Most Abantis are hill-toppers, mud lovers and are attracted by dead animals (fish and turtles), although some of them are also flower-visiting.